Direct electrochemistry of pentachlorophenol hydroxylase - Xie, W; Jones, J; Wong, L; Hill, H (2001)
The direct electrochemistry of the flavin-containing monooxygenase, pentachlorophenol hydroxylase (PCPH), at an edge plane graphite electrode was observed and a catalytic response, linear with concentration, was found with the substrate pentachlorophenol (PCP).